Outcomes of Treatment for Cervical Cancer Stage IB2 and IIA2; Radical Hysterectomy and Definitive Radiotherapy - Teeraphong Narukon; Suphet Tuipae; Pathomphorn Siraprapasiri (The Royal Thai College of Obstetricians and Gynaecologists, 2010)
Objective: To assess the outcomes and complications between radical hysterectomy and definitive radiotherapy in patients with cervical cancer stage IB2 and IIA2Materials and Methods: A retrospective analysis of patients with cervical cancer stage IB2 and IIA2 between January 2000 to June 2007 at Rajavithi Hospital was performed. The primary outcome measured were 3-year overall survival rates, 3-year progression free survival rate and the rate of complication. Patients with previous treatment from other hospitals, concurrent pregnancy and concurrent malignant disease were excluded from this study. Survival rate was analyzed by Kaplan Meier method.Result: Two hundred and nineteen patients with cervical cancer stage IB2 (n=91) and IIA2 (n=128) were enrolled. Ninety-eight patients (45%) underwent primary surgery (radical hysterectomy with/without adjuvant therapy) and121 patients (55%) underwent definitive radiotherapy (Radiation alone or concurrent chemoradiation). The 3-year progression free survival rate was 88.9% in primary surgery group and 90.4% in definitive radiotherapy group (P=0.952). The 3-year overall survival rates were 90.6% and 80.7%, respectively (P=0.057).The recurrence rate was 13.3% and 10.7% (P= 0.402). Major complications are not difference in both groups.Conclusion: Treatment modalities both of primary surgery and definitive radiotherapy are adequate treatment of cervical cancer stage IB2 and IIA2. The major complications and recurrent rate are not different.